Aktualisasi Penggunaan Metode dan Pengembangan Materi Nahwu di Pondok Pesantren Salafi Al-Fathaniyyah Serang - Mochamad Muizzuddin (The Arabic Education Department Postgraduate Programs, UIN Sultan Maulana Hasanuddin Banten in Partnership with PPJKBA Indonesia, 2021)
The background of the problem of the number of students studying Nahwu material shows that the Nahwu learning method tends to memorize the Nazham verse and the development of Nahwu material which tends to be traditional and editorial which is not functional and not contextual. This study aims to make an inventory of the Nahwu learning method developed at the Al-Fathaniyyah Islamic boarding school in Serang and the development of the Nahwu material developed at the Al-Fathaniyyah Islamic boarding school in Serang. Identifying the Nahwu learning method used by the Nahwu instructor and the development of the Nahwu. a Nahwu learning material developed in the classroom for students at the Al-Fathaniyah Islamic boarding school. This research methodology used an expository survey approach. This approach is carried out to describe the Nahwu learning method used by Nahwu instructors at the Al-Fathaniyyah Islamic boarding school and the development of Nahwu material that is conveyed to students in receiving Nahwu material which can be meaningful to students and teacher. Data collection techniques were obtained from interviews and observations of researchers in the field. The results of the study found that the Nahwu learning method in the process of delivering the Nahwu material is the al-tharîqah al-qiyâsiyyah method (deductive method). The process of presenting Nahwu material with the books studied at the Al-Fathaniyyah Islamic boarding school includes Jurûmiyyah, Matan Binâ, Mutammimah, 'Awâmil, and Matan Alfiyyah. The Nahwu first, then followed by examples that can clarify the rules that have been learned. Meanwhile, the development of Nahwu material as the